Traumatic Experiences of Female Victims of Sexual Harassment: A Case Study at Higher Education in South Sulawesi, Indonesia - Ulfa Rahmadani; Nur Afiah; Astinah Astinah; Ulfah Ulfah (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2026)
This research employed a qualitative case study design involving four female students and alums who experienced sexual harassment in higher education settings. Data were collected through in-depth semi-structured interviews and non-participant observation over six months. Thematic analysis was conducted using systematic coding to identify patterns across emotional, cognitive, behavioral, social, and academic dimensions. The findings reveal that sexual harassment generates persistent and interconnected psychological changes. Participants experienced intense emotional distress, including fear, shame, anxiety, and prolonged sadness. Cognitive distortions such as self-blame, negative self-perception, and lowered self-esteem were prominent. Behavioral responses included social withdrawal, avoidance of specific places or individuals, sleep disturbances, and self-harm tendencies. Social relationships deteriorated, particularly in interactions with male peers. Academic functioning was also disrupted, marked by decreased participation, difficulty concentrating, and delayed completion of academic tasks. Sexual harassment constitutes a complex and enduring traumatic experience that affects victims across multiple life domains. Trauma should be understood not only as an individual psychological response but also as a socially shaped experience. From a theoretical perspective, trauma theory explains that traumatic experiences are influenced not only by internal psychological processes but also by social contexts, including cultural norms, social support, and societal responses toward victims. Higher education institutions must adopt comprehensive, trauma-informed policies and support systems to ensure victim protection and recovery.